The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.5152/tjg.2019.18775
|View full text |Cite
|
Sign up to set email alerts
|

Impaired thiol/disulfide homeostasis in patients with mild acute pancreatitis

Abstract: Background/Aims: The aim of this study was to compare the dynamic thiol/disulfide (SS) homeostasis and ischemia-modified albumin (IMA) concentration between healthy subjects and patients with mild acute pancreatitis (AP). Materials and Methods: A total of 28 patients with AP (AP group) and 35 age-and sex-matched healthy individuals (control group) were included in this study. Serum thiols/SS and IMA concentrations were measured and compared between the two groups. Results: The mean serum native thiol (SH) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This study demonstrated that sh levels were significantly lower in AP patients than in healthy volunteers. Studies on thiol/disulfide parameters in AP patients have shown similar results to our study (1,6,8). However, Özyazıcı et al studied thiol/disulfide parameters among AP patients and showed that sh levels were significantly lower in AP patients than in control group patients (13).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study demonstrated that sh levels were significantly lower in AP patients than in healthy volunteers. Studies on thiol/disulfide parameters in AP patients have shown similar results to our study (1,6,8). However, Özyazıcı et al studied thiol/disulfide parameters among AP patients and showed that sh levels were significantly lower in AP patients than in control group patients (13).…”
Section: Discussionsupporting
confidence: 86%
“…TDH can easily be measured with an automated assay, described by Erel et al in 2014 (7). Many studies have reported on thiol levels and TDH in different diseases, such as coronary artery disease, ulcerative colitis, and AP (8). This study aimed to evaluate the role of TDH in the differential diagnosis of AP and predict the clinical severity among patients diagnosed with the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, deterioration of oxidative balance could cause abnormalities at structural and functional levels. 6,[9][10][11][12][13][14][15] In the literature, change in the thiol/disulphide homeostasis has been shown in diabetes mellitus, cardiovascular disorders, malignancy, rheumatoid arthritis, adenoid hypertrophy, acute pancreatitis, otitis media, β -thalassemia major, placenta percreta, inflammatory bowel diseases, rosacea and chronic kidney failure. [9][10][11][12][13][14][15] Another study by Atasever et al also investigated the thiol/disulphide homeostasis in ovarian torsion.…”
Section: Discussionmentioning
confidence: 99%
“…In order to calculate the sample size required by the study, a G*Power analysis was performed based on the results of a previous study 11 . Taking the target alpha (α) and 1 − beta (β) error levels as 0.05 and 0.95, respectively, it was determined a minimum of 34 participants were required for each group (68 in total) to achieve 95% power.…”
Section: Methodsmentioning
confidence: 99%